The Zangazur Corridor as the new haulage hub for integration and cooperation in the South Caucasus - Muhammad Gulahmadov; Ramil Huseyn (Business & IT, 2023)
This paper examines the economic significance of the South Caucasus' Zangazur Corridor in terms of achieving long-term peace, connectivity and integration in the region, and boosting regional growth. It further claims that the Zangazur Corridor will aid future South Caucasus reconciliation and economic cooperation.Upon the signing of the declaration, the establishment of the Zangazur corridor became even more critical. The Zangazur Corridor will connect the Republic of Azerbaijan and the Nakhchivan Autonomous Republic via the Republic of Armenia's Meghri area. The route was important in regional and international railway and highway transportation between Azerbaijan, Armenia, Iran, Turkey, and Russia during the Soviet era. However, the conflict between Armenia and Azerbaijan disrupted transportation for thirty years. The transportation links will then be extended from China to Europe. The Zangazur Corridor will play a vital part in the construction of East-West and North-South haulage. Many countries will benefit from the restoration of railways and roadways in the future. Hence, the study discusses the prospect of utilizing the Zangezur corridor - which is specified in the tripartite agreement dated 10 November 2020 - and emphasizes its significance as a vital element of the international transport network.